Armenian fragment of the lost treatise De numeris by Philo (Circe de clásicos y modernos, 2023)
We present the translation with commentary of a fragment in Armenian, published for the first and only time, with an English translation, by Abraham Terian, in 1984, which has no parallel in the Greek corpus of Philo. We describe the long path that the text traveled from its translation from original language to Armenian in the 6th century until it reaches to us. We make a brief reference to the importance of the Philonic conception on the decade according Pythagorean arithmology. We conclude with the reasons for the ascription of this fragment to the lost treatise De numeris.
Keywords: Armenian Philo; De numeris; Neopitagorism; Decad; mechitarists